COMMENCEMENT OF A NEW ROAD NETWORK IN THE KINGDOM OF POLAND IN THE PERIOD 1816-1817 - Marek RUTKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The main aim of this article is to introduce road repair and building programmes and procedures that took place in both the Kingdom of Poland, as a whole, and the Masovian Province, in particular. Starting with legal matters, this article describes the variety of combined activities on the part of the state government and local authorities undertaken between 1816 and 1817, which shaped the future development of Polish routes for many years to come.